Analog Metamorphosis Towards Mass Media Digitalization In Popular Culture Communication - muhamad, Pagi; Dwinarko, Dwinarko; Sjahfriza, Tabrani (Syntax Corporation, 2025)
The purpose of this research is to find out the efficiency of metamorphosis in the migration of analog communication to a digitized system of mass communication about popular culture and the political economy of mass media. economy of mass media. This research uses cultural theory with descriptive qualitative research methods. and narrative analysis based on literature data sources. The results of the study that the metamorphosis of analog media into digitalized media provides effective popular culture values for individuals and organizations in the use of mass communication media as social interaction, as well as the political economy of the media. Research recommendations on the communication role of organizational leaders in coordinating digitization systems in more creative digital management of popular culture in society.